PENGUATAN PENDIDIKAN AGAMA ISLAM BAGI SISWA MINORITAS MUSLIM - Suliantika Suliantika; Azizah Hanum OK (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Muslim minority students often face challenges in getting adequate Islamic religious education in a non-Muslim majority school environment. Sometimes, the majority does not recognise or respect the existence of minorities, which is not in line with the spirit of the nation that values diversity, especially in terms of religion and belief. This can lead to conflict. This research aims to examine how Islamic religious education is strengthened in minority areas through a qualitative approach. Data were collected through structured interviews, field observations and documentation collection. The results showed that the strengthening of Islamic religious education for Muslim minority students at SMP Negeri 1 Biru-Biru is done through religious activities such as worship practices, flash pesantren, Ramadhan Centre, and Halal Bi Halal events. Islamic Religious Education (PAI) teachers choose these activities to strengthen brotherhood and relationships between Muslim students, so that they can support each other in goodness despite being a minority. Tolerance is one of the main pillars in creating a peaceful environment between minority and majority